Clinician responses to cannabis use during pregnancy and lactation: a systematic review and integrative mixed-methods research synthesis. (16th November 2021) - Panday, Janelle; Taneja, Shipra; Popoola, Anuoluwa; Pack, Rachael; Greyson, Devon; McDonald, Sarah D; Black, Morgan; Murray-Davis, Beth; Darling, Elizabeth; Vanstone, Meredith
Abstract: Background: Perinatal cannabis use is increasing, and clinician counselling is an important aspect of reducing the potential harm of cannabis use during pregnancy and lactation. To understand current counselling practices, we conducted a systematic review and integrative mixed-methods synthesis to determine "how do perinatal clinicians respond to pregnant and lactating patients who use cannabis?" Methods: We searched 6 databases up until 2021-05-31. Eligible studies described the attitudes, perceptions, or beliefs of perinatal clinician about cannabis use during pregnancy or lactation. Eligible clinicians were those whose practice particularly focusses on pregnant and postpartum patients. The search was not limited by study design, geography, or year. We used a convergent integrative analysis method to extract relevant findings for inductive analysis. Results: Thirteen studies were included; describing perspectives of 1, 366 clinicians in 4 countries. We found no unified approach to screening and counselling. Clinicians often cited insufficient evidence around the effects of perinatal cannabis use and lacked confidence in counselling about use. At times, this meant clinicians did not address cannabis use with patients. Most counselled for cessation and there was little recognition of the varied reasons that patients might use cannabis, and an over-reliance on counselling focussed on the legal implications of use. Conclusion: Current approaches to responding to cannabis use might result in inadequate counselling. Counselling may be improved through increased education and training, which would facilitate conversations to mitigate the potential harm of perinatal cannabis use while recognizing the benefits patients perceive. Lay Summary: Cannabis use during pregnancy and breastfeeding is common and understanding current physician counselling approaches is important to identify gaps and to make suggestions for practice. We conducted a systematic review of the literature to understand how physicians respond to pregnant or breastfeeding patients who use cannabis. We found 13 eligible articles in our review and our analysis showed that there was no common approach to screening and counselling patients. Physicians often described needing more training and education to support their confidence. Additionally, physicians often did not address the various medical reasons for which patients might use cannabis during pregnancy and breastfeeding. We suggest that counselling approaches may be improved through increased education and training. This could facilitate conversations to help mitigate the potential harm of cannabis use while recognizing the benefits patients perceive and thus establish strong patient–physician relationships.